Relationship between Age and Standing Diameter of Eucalyptus pellita F. Muell Clone A in Industrial Plantation Forest Sebulu Kutai Kartanegara District, East Kalimantan Province: Hubungan Umur dengan Diameter Tegakan Eucalyptus pellita F. Muell Klon A di Hutan Tanaman Industri Kecamatan Sebulu Kutai Kartanegara Provinsi Kalimantan Timur - noor jannah; Marjenah; Wahjuni Hartati; Ria Rachel Paranoan (Agrifarm : Jurnal Ilmu Pertanian, 2020)
Forestry development which is oriented towards meeting the raw materials of the forestry industry is one of them with industrial plantations. The types developed are adapted to the needs of the industry and which have high economic value. Eucalyptus pellita F. Muell is one of the fast growing species that is very important for the pulp and paper industry. The advantages of this Eucalyptus as a fast growing plant are short rotation, few disease attacks, many benefits, and high economic value. One of the parameters of vegetative growth is the diameter, which in this case is measured by different stand age classes. So the research aims to determine the effect of age on the distribution of diameters and suspect of relationship patterns. The plant material is derived from clones, namely Clone A which is the result of selection from progeny test which will produce selected clones based on specified criteria and one of them is Clone A which is now a commercial clone since 2012. Propagation through vegetative tissue culture (as mother plant) which is then made shoot cuttings in the stool plant. The study was conducted in HTI PT Surya Hutani Jaya (PT SRH) Sebulu District, Kutai Kartanegara Regency, East Kalimantan Province by determining the research plots by purposive sampling with RAK ​​and 3 replications. Furthermore, doing a diameter census (DSD) and numbering of all tree compilers stands in a circular research plot with an area of ​​0.05 ha, circle radius 12.6 m on stands aged 6 months (0.5 years), 2, 4 and 5 years. The results obtained from this study which are based on the analysis of variance (ANOVA) shows that stand age has a very significant effect on the distribution of diameters, where the results of the BNT 5% test indicate that among the average diameters per age class (6 months, 2, 4 and 5 years) show significantly different from each other. The linear regression relationship between age and diameter distribution of the average stand formed with the equation formed was: Y = 3.96 + 2.2777X, with values ​​R2 = 0.9730 and r = 0.9864.